Bioremediation of cattle manure using microalgae after pre-treatment with biomass ash. (June 2021) - Viegas, Catarina; Gouveia, Luísa; Gonçalves, Margarida
Abstract: In this work, cattle manure was diluted and pre-treated with biomass ash to yield a liquid fraction and a solid precipitate. Microalgae grown in the liquid fraction, in batch and semi-continuous mode, achieved maximum biomass productivities of 522.9 and 554.3 mg L −1 day −1 (12 days) for Chlorella protothecoides and Tetradesmus obliquus, respectively. Nutrient removal efficiency was highest for the semicontinuous mode with replacement of 10% of reactor volume every 48 h. The produced algal biomass was characterized for its nutrient composition. Both, algal biomass, and precipitate aqueous extracts, were evaluated as biostimulants for wheat and watercress seeds Increments in the germination index were 177% for wheat with Chlorella protothecoides and 34% for watercress with Tetradesmus obliquus . The strategy adopted in this work is coherent with circular economy principles, combining effluent treatment with the production of added-value materials that could be used as biostimulants or animal feed additives. Graphical abstract: Unlabelled Image Highlights: Pretreatment of cattle manure reached 94% and 97% removal efficiency for COD and N. Solid precipitate sterilized and valorized as fertilizer Physico-chemical pre-treatment resulting in a transparent effluent Tetradesmus obliquus reached a productivity of 554 mg L −1 day −1 in semi-continuous mode. Chlorella protothecoides increased in 177% the wheat germination index.